Measurement of free radicals and their effects on human spermatozoa - Lampiao, Fanuel (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSCMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2006.